TRANSVERSE SYSTEMS ALONG THE EXTENSIONAL TYRRHENIAN MARGIN OF CENTRAL ITALY AND THEIR INFLUENCE ON VOLCANISM - Acocella V.; Funiciello R. (My University, 2006)
The Tyrrhenian margin of central Italy has undergone Plio-Quaternary extension, developing NW-SE normal faults and NE-SW faults. The NE-SW faults decrease in frequency toward NE with the stretching factor β, becoming negligible for β < 1.3. Plio-Quaternary volcanoes, aligned NW-SE, formed at the intersection among NE-SW and NW-SE faults; fissure eruptions are mostly controlled by NE-SW faults. Structural field data show normal motions for 76% of NW-SE Quaternary faults and transtensive for 73% of NE-SW Quaternary faults. Analogue experiments simulating the NE-SW Tyrrhenian extension show that transverse transtensive faults form with differential extension Δβ > 0.21. These data suggest that the NE-SW transtensive structures are transfer faults of the NW-SE normal faults due to relevant differential extension (Δβ > 0.21) within a stretched crust (β > 1.3). The minor dip-slip and strikeslip components of the NE-SW and NW-SE faults, respectively, possibly result from the NW-SE extension due to the southeastward slab retreat beneath the Calabrian arc. The NE-SW and NW-SE extensions in the central southern Tyrrhenian Sea account for the composite kinematics of the NE-SW structures, which, in turn, exert a twofold role in controlling volcanism. Where their dip-slip component forms basins, the associated decompression induces magma accumulation (developing central volcanoes) at the intersection among NW-SE and NE-SW systems. Where transfer faults are mainly strike slip, their inferred subvertical attitude enhances their permeability to magma, accounting for the observed NE-SW fissure eruptions. Regional extension, forming NW-SE faults, enhances the overall generation and rise of magma along the margin, but NE-SW structures focus magma rise and emplacement at shallower levels. Copyright 2006 by the American Geophysical Union.
Keywords: Quaternary; Cenozoic::Quaternary; Четвертичный